State Employment Agency of Latvia Training Event in Conformity with the Labor Market Needs - Barbare, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
State Employment Agency (SEA) 2011 initiated a conceptual shift away from a short-term crisis management approach to long-term labor market policy measures, which include changes to the range of training activities and organization. The goal of this research paper is to ensure the SEA training aligns with labor market needs, and offers assessment and proposals for their improvement. This paper covers the training relevance assessment according to labor market needs, analyses SEA customer demand, awareness and satisfaction regarding the training events, provides guidance on the counselors' role and its impact, as well as assessment of the coupon method. The objective of the study was to use a variety of data collection and analysis methods: an analysis of policy documents, statistical data analysis, a secondary analysis of previous research, database analysis, telephone interviews, focus group discussions and expert discussions.